Mini-review of Phytochemistry for Polyalithia longiflia - Mudhafar, Mustafa; Zainol, Ismail; Desa, Shakinaz; Jaafar, Che Nor Aziza (Moment Publications, 2019)
The review was aimed to review the phytochemical of the Polyalithia longiflia. Phytochemical screening for all parts of Polyalithia longiflia have been done and shown most of the chemical group compounds such as glycosides, Sterol, Carbohydrates, terpenoids, flavonoids. 174compounds have been isolated from five parts (leaves, steam bark, seeds, fruits, root) of Polyalithia longiflia, these compounds have been drown their structure. Leaves of Polyalithia longiflia were extracted and isolated 99 compounds most of these compounds were terpenoids, 59 compounds were isolated from the stem bark belong to different chemical groups such as Terpenoids, Alkaloids, Phenol, Fatty acids, and Steroids, 16 compounds were isolated from the fruit from several chemicals groups, 11 compounds were isolated from the root,7 compounds were isolated from the seeds which belong to different chemical groups which are Terpenoids, Fatty Acids, and Carbohydrate. Many of these compound have been used in medical filed in many applications due to their activities which make this plant very important in medicine filed. Root of Polyalithialongiflia only three articles about it. Also seeds of Polyalithia longiflia have not been studied yet its phytochemical screening. The compounds have been drown with chemdrow application, and with PubChem.